Disruption of a C69-Family Cysteine Dipeptidase Gene Enhances Heat Shock and UV-B Tolerances in Metarhizium acridum - Li, Juan; Guo, Mei; Cao, Yueqing; Xia, Yuxian (Frontiers in Microbiology, 2020)
In fungi, peptidases play a crucial role in adaptability. At present, the roles of peptidases in Ultraviolet (UV) and thermal tolerance are still unclear. In this study, a C69-family cysteine dipeptidase of the entomopathogenic fungus Metarhizium acridum, MaPepDA, was expressed in Escherichia coli. The purified enzyme had a molecular mass of 56-kDa, and displayed a high activity to dipeptide substrate with an optimal Ala-Gln hydrolytic activity at about pH 6.0 and 55 °C. It was demonstrated that MaPepDA is an intracellular dipeptidase localized in the cytosol, and that it is expressed during the whole fungal growth. Disruption of the MaPepDA gene increased conidial germination, growth rate, and significantly improved the tolerance to UV-B and heat stress in M. acridum. However, virulence and conidia production was largely unaffected in the ΔMaPepDA mutant. Digital gene expression data revealed that the ΔMaPepDA mutant had a higher UV-B and heat-shock tolerance compared to wild type by regulating transcription of sets of genes involved in cell surface component, cell growth, DNA repair, amino acid metabolism, sugar metabolism and some important signaling pathways of stimulation. Our results suggested that disruption of the MaPepDA could potentially improve the performance of fungal pesticides in the field application with no adverse effect on virulence and conidiation.